Family structures and parents’ occupational models: its impact on children’s diabetes - Schlarb, Pauline; Büttner, Janina M.; Tittel, Sascha R.; Mönkemöller, Kirsten; Müller-Godeffroy, Esther; Boettcher, Claudia; Galler, Angela; Berger, Gabriele; Brosig, Burkhard; Holl, Reinhard W.; Justus Liebig University Giessen (My University, 2023)
Aims: This study examines how family-related factors influence the management of children and adolescents with type 1 diabetes (T1DM). We investigate the relationship between family patterns, parental work schedules and metabolic control. Materials and methods: We analysed data from a nationwide diabetes survey (DPV) focusing on HbA1c, severe hypoglycaemia, diabetic ketoacidosis, hospital admissions and inpatient treatment duration. We used linear regression and negative binomial regression models. Our study includes 15,340 children under the age of 18 with data on family structure and parental division of labour. Results: Children from two-parent households have better HbA1c outcomes than children from single-parent, blended or no-parent households (p < .0001). Higher HbA1C levels are associated with children living with an unemployed father, as opposed to those with full-time working parents or with a full-time working father and a part-time working mother (p < .001). Conclusions: These findings emphasise the importance of carefully considering family structure and working time models in the management of paediatric T1DM. Our results highlight risk factors within the family environment and emphasise the need for family-focused counselling of high-risk patients or severe cases in clinical practice.
Keywords: ddc:610